2018
DOI: 10.3389/fphys.2018.00445
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation During ACL Injury Risk Movements in Young Female Athletes: A Narrative Review

Abstract: Young, adolescent female athletes are at particular high risk of sustaining a non-contact anterior cruciate ligament (ACL) injury during sport. Through the last decades much attention has been directed toward various anatomical and biomechanical risk factors for non-contact ACL injury, and important information have been retrieved about the influence of external loading factors on ACL injury risk during given sports-specific movements. However, much less attention has been given to the aspect of neuromuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 78 publications
1
61
0
1
Order By: Relevance
“…One study examined muscle activation patterns as an isolated risk factor for noncontact ACL injury 185 and showed reduced EMG pre-activity of the semitendinosus muscle and increased pre-activity of the vastus lateralis muscle before side-cutting in female handball and football players who later had a noncontact ACL injury compared to players who remained uninjured 185 . This study underlines the importance of medial hamstring muscle activation for the prevention of ACL injuries 14 .…”
Section: Risk Factors For Injurysupporting
confidence: 53%
See 2 more Smart Citations
“…One study examined muscle activation patterns as an isolated risk factor for noncontact ACL injury 185 and showed reduced EMG pre-activity of the semitendinosus muscle and increased pre-activity of the vastus lateralis muscle before side-cutting in female handball and football players who later had a noncontact ACL injury compared to players who remained uninjured 185 . This study underlines the importance of medial hamstring muscle activation for the prevention of ACL injuries 14 .…”
Section: Risk Factors For Injurysupporting
confidence: 53%
“…In a study of female football and handball players, increased pre-activity of the medial hamstring muscle was seen after a period of IPEP training 184,186 . We do not know, however, how long these adaptations will be sustained in the absence of training or as the athletes get older and more mature 14 . One study showed that changed movement patterns after a three-month intervention were not retained, whereas movement patterns after a twelve-month intervention were, indicating the importance of long intervention periods 132 .…”
Section: Effect Mechanisms Of Injury Prevention Exercise Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies aimed at identifying neuromuscular injury risk factors 118 are likely important for reducing ACL injury risk. Injury risk factor identification from athlete pre-season isokinetic strength assessments seems to play only a minor role in the prevention of ACL injury 119 or hamstring strain.…”
Section: Modifiable Neuromuscular and Physiological Risk Factorsmentioning
confidence: 99%
“…Neuromuscular control is a risk factor that plays an important role in non-contact injury 6,10 , as it exhibits a sex dimorphism [16][17][18][19][20] and may be modifiable through training [45][46][47] .…”
mentioning
confidence: 99%